Imitation of meaningless gestures in normal aging. Issue 5 (2nd September 2020) - Baumard, Josselin; Lesourd, Mathieu; Remigereau, Chrystelle; Lucas, Charlène; Jarry, Christophe; Osiurak, François; Le Gall, Didier
ABSTRACT: While imitation of meaningless gestures is a gold standard in the assessment of apraxia in patients with either stroke or neurodegenerative diseases, little is known about potential age-related effects on this measure. A significant body of literature has indicated that different mechanisms (i.e., executive functioning, visuospatial skills, sensory integration, body knowledge, categorical apprehension) may underlie the performance depending on imitation conditions (i.e., finger/hand, uni-/bimanual, symmetric/asymmetric, crossed/uncrossed configurations). However, neither the effects of these conditions on performance, nor the contribution of the abovementioned mechanisms to imitation have been explored in normal aging. The aim of the present study was to fill this gap. To do so, healthy adults ( n = 103) aged 50 to 89 were asked to imitate 45 meaningless gestures. The authors controlled for general cognitive function, motor function, visual-spatial skills, executive function, sensory integration, body knowledge, and mechanical problem-solving skills. The results showed that asymmetry, body-midline crossing and, to a lesser extent, bimanual activity added an additional layer of difficulty to imitation tasks. After controlling for motor speed and cognitive function, age had an effect on imitation skills after 70 years old. This may reflect a decline in body knowledge, sensory integration, and executive functions. In contrast, the visuospatial and mechanical problem-solving hypotheses were ruled out. An additional motor simulation hypothesis is proposed. These findings may prove useful for clinicians working in memory clinics by providing insights on how to interpret imitation deficits. Lower performance after 70 years old should not be considered abnormal in a systematic manner.